Effect of Er:YAG Laser on Shear Bond Strength of Composite to Enamel and Dentin of Primary Teeth - Zahra Bahrololoomi; Mona Kabudan; Leila Gholami (Tehran University of Medical Sciences, 2015)
Objectives: Bond strength of composite resin to enamel and dentin of primary teeth is lower than that to permanent teeth; therefore, it may compromise the ad- hesive bonding. New methods, such as laser application have been recently intro- duced for tooth preparation. The purpose of this study was to evaluate the effect of tooth preparation with bur and Er:YAG laser on shear bond strength of com- posite to enamel and dentin of primary teeth. Materials and Methods: Seventy-five primary molar teeth were collected and 150 specimens were obtained by mesiodistal sectioning of each tooth. In each of the enamel and dentin groups, the teeth were randomly assigned to 3 subgroups with the following preparations: bur preparation + etching (37% H3PO4), laser preparation + etching, and laser preparation without etching. Single Bond adhe- sive and Z250 composite were applied to all samples. After thermocycling, the shear bond strength testing was preformed using the Instron Testing Machine. Data were analysed using SPSS-17 and two-way ANOVA. Results: The bond strength of enamel specimens was significantly higher than that of dentin specimens, except for the laser-non-etched groups. The enamel and dentin laser-non-etched groups had no significant difference in bond strength. In both enamel and dentin groups, bur preparation + etching yielded the highest bond strength, followed by laser preparation + etching, and the laser preparation with- out etching yielded the lowest bond strength (P < 0.001). Conclusion: In both enamel and dentin groups, laser preparation caused lower shear bond strength compared to bur preparation.